On the origin of the late-flowering ppd-H1 allele in barley - Rajiv Sharma; Salar Shaaf; Kerstin Neumann; Peter Civan; Yu Guo; Martin Mascher; Michal David; Adnan Al-Yassin; Hakan Özkan; Tom Blake; Sariel Hübner; Nora P. Castañeda-Álvarez; et al. (Theoretical and Applied Genetics, 2025)
To breed for climate resilient crops, an understanding of the genetic and environmental factors influencing adaptation is critical. Barley provides a model species to study adaptation to climate change. Here we present a detailed analysis of genetic variation at a major photoperiod response locus and relate this to the domestication history and dispersal of barley. The PPD-H1 locus (a PSEUDO-RESPONSE REGULATOR 7 ) promotes flowering under long-day conditions, and a natural mutation at this locus resulted in a recessive, late-flowering ppd-H1 allele. This mutation proved beneficial in high-latitude environments such as Northern Europe, where it allows extended vegetative growth during long spring days. We infer the origin of the mutated late-flowering ppd-H1 allele by re-sequencing a large geo-referenced collection of 942 Hordeum spontaneum , 5 Hordeum agriocrithon and 1110 domesticated ( Hordeum vulgare ) barleys. We demonstrate that the late-flowering phenotype originated from Desert-type wild barley in the Southern Levant and present evidence suggesting a post-domestication origin of the mutated ppd-H1 allele.

Prescribed burning as a potential regeneration technique for reed stands: a pilot study in the reed belt of Lake Neusiedl, Austria - Raffael Berner; Mathias Neumann; Mortimer Müller; Markus Hollaus; Andreas Maier; Thomas Zechmeister; Stephan Glatzel (Wetlands Ecology and Management, 2025)
Nature conservation calls for the management of reed in large stands to support the rejuvenation of reed. Traditional reed management tools at Lake Neusiedl are becoming decreasingly suitable due to insufficient freezing in winter. Therefore, prescribed burning of old Phragmites australis stands is currently being considered as a regeneration measure to promote reed regrowth and maintain invaluable habitats for specialized species in the reed belt. In January 2024 a pilot study was carried out near the municipality of Jois to gain insights into suitability and consequences of controlled burning of old reed mats in the reed belt. Applied methods include pre- and post-fire biomass and carbon content analyses from vegetation, litter and soil, fire behavior and intensity monitoring, moisture content measurements during and after the fire, and area-wide UAV-LiDAR mapping. Mean fire temperature was approx. 700 °C and peaked at 1034 °C. 15.57 ha of the 32 ha study area were affected by the fire, and a total of 57.84 tons of carbon were released (3.72 t C/ha). On burnt areas standing vegetation was removed and litter thickness significantly reduced by approx. 30%, while no biomass loss from soil was detected. Fuel moisture content is negatively correlated to distance from the water table and has mitigating effects on fire spread if above 30%, resulting in unaffected deeper layers and numerous unburnt refugia patches within the fire perimeter. Our results indicate that prescribed fire can be a suitable management tool at Lake Neusiedl for the purpose of reed rejuvenation and wetland habitat regeneration.

Nitrogen isotope homogenization of dissolved ammonium with depth and 15N enrichment of ammonium during incorporation into expandable layer silicates in organic-rich marine sediment from Guaymas Basin, Gulf of California - Toshiro Yamanaka; Arisa Sakamoto; Kanon Kiyokawa; Jaeguk Jo; Yuji Onishi; Yoshihiro Kuwahara; Ji-Hoon Kim; Lucie C. Pastor; Andreas Teske; Daniel Lizarralde; Tobias W. Höfig; Ivano W. Aiello; et al. (Chemical Geology, 2024)

Mineralization kinetics of biosiliceous sediments in hot subseafloors - Ivano W. Aiello; Tobias W. Höfig; Armelle Riboulleau; Andreas P. Teske; Daniel Lizarralde; Jeanine L. Ash; Diana P. Bojanova; Martine D. Buatier; Virginia P. Edgcomb; Christophe Y. Galerne; Swanne Gontharet; Verena B. Heuer; et al. (Geochimica et Cosmochimica Acta, 2024)

Schauerella fraxinea gen. nov., sp. nov., a bacterial species that colonises ash trees tolerant to dieback caused by Hymenoscyphus fraxineus - Undine Behrendt; Valentin Burghard; Sonja Wende; Kristina Ulrich; Jacqueline Wolf; Meina Neumann-Schaal; Andreas Ulrich (Systematic and Applied Microbiology, 2024)

Melatonin priming manipulates antioxidant regulation and secondary metabolites production in favour of drought tolerance in Chenopodium quinoa Willd. - Maryam Samadi; Seyed Abdolreza Kazemeini; Fatemeh Razzaghi; Mohsen Edalat; Mathias Neumann Andersen; Sven-Erik Jacobsen; Andrea Mastinu (South African Journal of Botany, 2024)

Sedimentary mud and phaeophytin-a are reliable predictors of oxygen consumption and nitrogen turnover in the southern North Sea - Fabrizio Minutolo; Kirstin Dähnke; Marc Metzke; Moritz Holtappels; Andreas Neumann (Continental Shelf Research, 2024)

The interplay of temperature and algal enrichment intensifies bioturbation of the intertidal amphipod Corophium volutator - Eilish M. Farrell; Jan Beermann; Andreas Neumann; Alexa Wrede (Journal of Experimental Marine Biology and Ecology, 2023)

Genetic diversity, distribution and domestication history of the neglected GGAtAt genepool of wheat - Ekaterina D. Badaeva; Fedor A. Konovalov; Helmut Knüpffer; Agostino Fricano; Alevtina S. Ruban; Zakaria Kehel; Svyatoslav A. Zoshchuk; Sergei A. Surzhikov; Kerstin Neumann; Andreas Graner; Karl Hammer; Anna Filatenko; et al. (Theoretical and Applied Genetics, 2022)
Key message We present a comprehensive survey of cytogenetic and genomic diversity of the GGA t A t genepool of wheat, thereby unlocking these plant genetic resources for wheat improvement. Abstract Wheat yields are stagnating around the world and new sources of genes for resistance or tolerances to abiotic traits are required. In this context, the tetraploid wheat wild relatives are among the key candidates for wheat improvement. Despite its potential huge value for wheat breeding, the tetraploid GGA t A t genepool is largely neglected. Understanding the population structure, native distribution range, intraspecific variation of the entire tetraploid GGA t A t genepool and its domestication history would further its use for wheat improvement. The paper provides the first comprehensive survey of genomic and cytogenetic diversity sampling the full breadth and depth of the tetraploid GGA t A t genepool. According to the results obtained, the extant GGA t A t genepool consists of three distinct lineages. We provide detailed insights into the cytogenetic composition of GGA t A t wheats, revealed group- and population-specific markers and show that chromosomal rearrangements play an important role in intraspecific diversity of T. araraticum . The origin and domestication history of the GGA t A t lineages is discussed in the context of state-of-the-art archaeobotanical finds. We shed new light on the complex evolutionary history of the GGA t A t wheat genepool and provide the basis for an increased use of the GGA t A t wheat genepool for wheat improvement. The findings have implications for our understanding of the origins of agriculture in southwest Asia.

Journal Club - Andreas Peschel; Andreas Diepold; Thilo M. Fuchs; Julia Ast; Marion Lemoine; Bernhard Schink; Kürşad Turgay; Bärbel Stecher; Kai Thormann; Remy Colin; Johannes Sander; Petra Neumann-Staubitz; et al. (BIOspektrum, 2022)

Correction to: Genetic diversity, distribution and domestication history of the neglected GGAtAt genepool of wheat - Ekaterina D. Badaeva; Fedor A. Konovalov; Helmut Knüpffer; Agostino Fricano; Alevtina S. Ruban; Zakaria Kehel; Svyatoslav A. Zoshchuk; Sergei A. Surzhikov; Kerstin Neumann; Andreas Graner; Karl Hammer; Anna Filatenko; et al. (Theoretical and Applied Genetics, 2021)

Genome sequencing in families with congenital limb malformations - Jonas Elsner; Martin A. Mensah; Manuel Holtgrewe; Jakob Hertzberg; Stefania Bigoni; Andreas Busche; Marie Coutelier; Deepthi C. de Silva; Nursel Elçioglu; Isabel Filges; Erica Gerkes; Katta M. Girisha; et al. (Human Genetics, 2021)
The extensive clinical and genetic heterogeneity of congenital limb malformation calls for comprehensive genome-wide analysis of genetic variation. Genome sequencing (GS) has the potential to identify all genetic variants. Here we aim to determine the diagnostic potential of GS as a comprehensive one-test-for-all strategy in a cohort of undiagnosed patients with congenital limb malformations. We collected 69 cases (64 trios, 1 duo, 5 singletons) with congenital limb malformations with no molecular diagnosis after standard clinical genetic testing and performed genome sequencing. We also developed a framework to identify potential noncoding pathogenic variants. We identified likely pathogenic/disease-associated variants in 12 cases (17.4%) including four in known disease genes, and one repeat expansion in HOXD13 . In three unrelated cases with ectrodactyly, we identified likely pathogenic variants in UBA2 , establishing it as a novel disease gene. In addition, we found two complex structural variants (3%). We also identified likely causative variants in three novel high confidence candidate genes. We were not able to identify any noncoding variants. GS is a powerful strategy to identify all types of genomic variants associated with congenital limb malformation, including repeat expansions and complex structural variants missed by standard diagnostic approaches. In this cohort, no causative noncoding SNVs could be identified.

Macrofauna as a major driver of bentho‐pelagic exchange in the southern North Sea - Andreas Neumann; Justus E. E. van Beusekom; Annika Eisele; Kay‐Christian Emeis; Jana Friedrich; Ingrid Kröncke; Ella Lu Logemann; Julia Meyer; Céline Naderipour; Ulrike Schückel; Alexa Wrede; Michael L. Zettler (Limnology and Oceanography, 2021)
The contribution of sediments to nutrient cycling of the coastal North Sea is strongly controlled by the intensity of fluxes across the sediment water interface. Pore‐water advection is one major exchange mechanism that is well described by models, as it is determined by physical parameters. In contrast, biotransport (i.e., bioirrigation, bioturbation) as the other major transport mechanism is much more complex. Observational data reflecting biotransport, from the German Bight for example, is scarce. We sampled the major sediment provinces of the German Bight repeatedly over the years from 2013 to 2019. By employing ex situ whole core incubations, we established the seasonal and spatial variability of macrofauna‐sustained benthic fluxes of oxygen and nutrients. A multivariate, partial least squares analysis identified faunal activity, in specifically bioturbation and bioirrigation, alongside temperature, as the most important drivers of oxygen and nutrient fluxes. Their combined effect explained 63% of the observed variability in oxygen fluxes, and 36–48% of variability in nutrient fluxes. Additional 10% of the observed variability of fluxes were explained by sediment type and the availability of plankton biomass. Based on our extrapolation by sediment provinces, we conclude that pore‐water advection and macrofaunal activity contributed equally to the total benthic oxygen uptake in the German Bight.

Cost‐effectiveness of longitudinal surveillance for Piscirickettsia salmonis using qPCR in Atlantic salmon farms ( Salmo salar ) in Chile - Marina K. V. C. Delphino; Fernando O. Mardones; Joaquin Neumann Heise; Alicia Gallardo; Daniel Jimenez; Andrea Peña; Marco Rozas‐Serri; Ian A. Gardner (Journal of Fish Diseases, 2021)
Costs of diagnostic testing including sample collection, sampling frequency and sample size are an important consideration in the evaluation of the economic feasibility of alternative surveillance strategies for detection of infectious diseases in aquatic animals. In Chile, Piscirickettsia salmonis is the primary reason for antibiotic treatments in farmed Atlantic salmon. In 2012, a surveillance and control programme for piscirickettsiosis was established with an overall goal of reducing antibiotic use. The present study estimated the cost‐effectiveness of different sampling frequencies and sample sizes to achieve at least 95% confidence of early detection of P. salmonis at the netpen and farm levels using a validated qPCR test. We developed a stochastic model that incorporated variability in test accuracy, within‐pen prevalence and sampling costs. Our findings indicated that the current piscirickettsiosis surveillance programme based on risk‐based sampling of five moribund or dead fish from 2 to 3 netpens is cost‐effective and gives a high probability of detection of P. salmonis in Atlantic salmon farms in Chile at both the netpen and farm levels. Results from this study should incentivize salmon farmers to establish cost‐effective strategies for early detection of P. salmonis infection and the application of this approach to other highly infectious diseases.

Detection of Colchicum autumnale in drone images, using a machine-learning approach - Lukas Petrich; Georg Lohrmann; Matthias Neumann; Fabio Martin; Andreas Frey; Albert Stoll; Volker Schmidt (Precision Agriculture, 2020)
Colchicum autumnale are toxic autumn-blooming flowering plants, which often grow on extensive meadows and pastures. Thus, they pose a threat to farm animals especially in hay and silage. Intensive grassland management or the use of herbicides could reduce these weeds but environment protection requirements often prohibit these measures. For this reason, a non-chemical site- or plant-specific weed control is sought, which aims only at a small area around the C. autumnale and with low impact on the surrounding flora and fauna. For this purpose, however, the exact locations of the plants must be known. In the present paper, a procedure to locate blooming C. autumnale in high-resolution drone images in the visible light range is presented. This approach relies on convolutional neural networks to detect the flower positions. The training data, which is based on hand-labeled images, is further enhanced through image augmentation. The quality of the detection was evaluated in particular for grassland sites which were not included in the training to get an estimate for how well the detector works on previously unseen sites. In this case, 88.6% of the flowers in the test dataset were detected, which makes it suitable, e.g., for applications where the training is performed by the manufacturer of an automatic treatment tool and where the practitioners apply it to their previously unseen grassland sites.

Demographic, physiological, psychological, and on-ice performance indicators predict plus/minus status of recreational ice hockey players across a season - Claudio R. Nigg; Andreas Gessner; Carina Nigg; Marco Giurgiu; Rainer Neumann (German Journal of Exercise and Sport Research, 2020)
Little is known about physical, physiological, and psychological performance indicators predicting recreational athletes’ performance. This information may motivate players to become more active and inform coaches where to focus to build confidence, cohesion, and cooperation. This study investigated which performance indicators were related to the plus-minus statistic in German recreational ice hockey players ( n = 20 players; 1 female; mean age = 36.25 ± 12.91 years; height = 178.85 ± 8.64 cm; weight = 81.36 ± 12.89 kg; mean years of ice hockey experience = 5.68 ± 8.93) over a season. Anthropometrics, psychological and on-ice performance data were collected mid-season and plus-minus were recorded after each game. Due to the small sample size, significance interpretations are not meaningful; therefore, Cohen’s guidelines were used for r = 0.2 (small), r = 0.5 (medium) and r = 0.8 (large). Medium size positive correlations of plus/minus were found for push-ups (r = 0.52) and squats (r = 0.37). Small positive correlations were found for shot speed (r = 0.33), competitiveness orientation (r = 0.28), and years on team (r = 0.23). Small negative correlations were found for win orientation (r = −0.30), body mass index (r = −0.28), task cohesion (r = −0.24), and percent body fat (r = −0.20). Some performance and psychological indicators are related to recreational ice hockey players’ plus-minus statistic over a season. Coaches and players of recreational teams should focus on muscular strength and endurance, shooting speed, body composition, and enjoying the challenge of competition while lowering their win orientation.

Correction to: Strength of correlation between wildlife collision data and hunting bags varies among ungulate species and with management scale - Wiebke Neumann; Fredrik Widemo; Navinder J. Singh; Andreas Seiler; Joris P. G. M. Cromsigt (European Journal of Wildlife Research, 2020)

Strength of correlation between wildlife collision data and hunting bags varies among ungulate species and with management scale - Wiebke Neumann; Fredrik Widemo; Navinder J. Singh; Andreas Seiler; Joris P. G. M. Cromsigt (European Journal of Wildlife Research, 2020)
Most European ungulate species are increasing in numbers and expanding their range. For the management and monitoring of these species, 64% of European countries rely on indirect proxies of abundance (e.g., hunting bag statistics). With increasing ungulate numbers, data on ungulate-vehicle collisions (UVC) may provide an important and inexpensive, complementary data source. Currently, it is unclear how bag statistics compare with UVC. A direct comparison of these two indices is important because both are used in ungulate management. We evaluated the relationship between UVC and ungulate hunting bags across bioclimatic, regional, and local scales, using five time lags (t −3 to t +1 ) for the five most common wild ungulate species in Sweden. For all species, hunting bags and UVC correlated positively, but correlation strength and time lags varied across scales and among species. The two indices correlated most strongly at the local management scale. Correlation between both indices was strong for the smaller deer species and wild boar, in particular, but much weaker for moose where we found the best fit using a 2-year time lag. For the other species, indices from the same year correlated best. We argue that the reason for moose data behaving differently is that, in Sweden, moose are formally managed using a 3-year time plan, while the other species are not. Accordingly, moose hunting bags are influenced more strongly by density-independent processes than bags of the other species. Consequently, the mismatch between the two indices may generate conflicting conclusions for management depending on the method applied.

Journal Club - Marisa Schübel; Klaus Hantke; Javier Garcia Varo; Andreas Seiffert-Störiko; Stefanie Schulz; Petra Neumann-Staubitz; Theresa Gewering; Daniela Kruck; Sylvia Schnell; Michael Steinert (BIOspektrum, 2020)

Bayesian estimation of diagnostic sensitivity and specificity of a qPCR and a bacteriological culture method for Piscirickettsia salmonis in farmed Atlantic salmon ( Salmo salar L.) in Chile - Emilie Laurin; Ian A. Gardner; Andrea Peña; Marco Rozas‐Serri; Jorge Gayosa; Joaquin Neumann Heise; Fernando O. Mardones (Journal of Fish Diseases, 2020)
Early detection of piscirickettsiosis is an important purpose of government‐ and industry‐based surveillance for the disease in Atlantic salmon farms in Chile. Real‐time qPCRs are currently used for surveillance because bacterial isolation is inadequately sensitive or rapid enough for routine use. Since no perfect tests exist, we used Bayesian latent class models to estimate diagnostic sensitivity ( DSe ) and specificity ( DSp ) of qPCR and culture using separate two‐test, single‐population models for three farms ( n = 148, 151, 44). Informative priors were used for DSp (culture (beta(999,1); qPCR (beta(98,2)), and flat priors (beta 1,1) for DSe and prevalence. Models were run for liver and kidney tissues combined and separately, based on the presence of selected gross‐pathological signs. Across all models, qPCR DSe was 5‐ to 30‐fold greater than for culture. Combined‐tissue qPCR median DSe was highest in Farm 3 (sampled during P. salmonis outbreak ( DSe = 97.6%)) versus Farm 1 ( DSe = 85.6%) or Farm 2 ( DSe = 83.5%), both sampled before clinical disease. Median DSe of qPCR was similar for liver and kidney, but higher when gross‐pathological signs were evident at necropsy. High DSe and DSp and rapid turnaround‐time indicate that the qPCR is fit for surveillance programmes and diagnosis during an outbreak. Targeted testing of salmon with gross‐pathological signs can enhance DSe .

Comparison of three types of laser optical disdrometers under natural rainfall conditions - Lisbeth Lolk Johannsen; Nives Zambon; Peter Strauss; Tomas Dostal; Martin Neumann; David Zumr; Thomas A. Cochrane; Günter Blöschl; Andreas Klik (Hydrological Sciences Journal, 2020)

Anti-inflammatory effects of Phaeodactylum tricornutum extracts on human blood mononuclear cells and murine macrophages - Ulrike Neumann; Sandrine Louis; Andrea Gille; Felix Derwenskus; Ulrike Schmid-Staiger; Karlis Briviba; Stephan C. Bischoff (Journal of Applied Phycology, 2018)

Use of high-throughput RT-qPCR to assess modulations of gene expression profiles related to genomic stability and interactions by cadmium - Bettina Maria Fischer; Daniel Neumann; Ann Liza Piberger; Sarah Fremgaard Risnes; Beate Köberle; Andrea Hartwig (Archives of Toxicology, 2016)

Aquifer community structure in dependence of lithostratigraphy in groundwater reservoirs - Andrea Beyer; Michael Rzanny; Aileen Weist; Silke Möller; Katja Burow; Falko Gutmann; Stefan Neumann; Julia Lindner; Steffen Müsse; Hanka Brangsch; Jennifer Stoiber-Lipp; Martin Lonschinski; et al. (Environmental Science and Pollution Research, 2015)

Y-P30 promotes axonal growth by stabilizing growth cones - Janine R. Neumann; Suvarna Dash-Wagh; Kay Jüngling; Teresa Tsai; Martin Meschkat; Andrea Räk; Sabine Schönfelder; Christian Riedel; Mohammad I. K. Hamad; Stefan Wiese; Hans-Christian Pape; Kurt Gottmann; et al. (Brain Structure and Function, 2015)

Diversity of germination and seedling traits in a spring barley (Hordeum vulgare L.) collection under drought simulated conditions - Adel H. Abdel-Ghani; Kerstin Neumann; Celestine Wabila; Rajiv Sharma; Sidram Dhanagond; Saed J. Owais; Andreas Börner; Andreas Graner; Benjamin Kilian (Genetic Resources and Crop Evolution, 2015)

A simple model for the estimation of wine characteristics in SW Germany - Paul A. Neumann; Andreas Matzarakis (Theoretical and Applied Climatology, 2014)

Estimation of wine characteristics using a modified Heliothermal Index in Baden-Württemberg, SW Germany - Paul A. Neumann; Andreas Matzarakis (International Journal of Biometeorology, 2014)

Histamine induces chemotaxis and phagocytosis in murine bone marrow-derived macrophages and RAW 264.7 macrophage-like cells via histamine H4-receptor - Christoph P. Czerner; Andreas Klos; Roland Seifert; Detlef Neumann (Inflammation Research, 2014)

Differential influenza H1N1-specific humoral and cellular response kinetics in kidney transplant patients - Vinay Rambal; Karin Müller; Chantip Dang-Heine; Arne Sattler; Mikalai Dziubianau; Benjamin Weist; Si-Hong Luu; Alexandra Stoyanova; Peter Nickel; Andreas Thiel; Avidan Neumann; Brunhilde Schweiger; et al. (Medical Microbiology and Immunology, 2014)

Darbepoetin inhibits proliferation of hepatic cancer cells in the presence of TGF-β - Sabrina Ehnert; Thomas Freude; Carmen Eicher; Britta Burkhardt; Juan J. Martínez Sánchez; Jan Neumann; Ruben Mühl-Benninghaus; Steven Dooley; Stefan Pscherer; Andreas K. Nussler (Archives of Toxicology, 2014)

Molecular markers in management of ex situ PGR – A case study - Andreas Börner; Elena K Khlestkina; Sabina Chebotar; Manuela Nagel; Mian Abdur Rehman Arif; Kerstin Neumann; Borislav Kobiljski; Ulrike Lohwasser; Marion S Röder (Journal of Biosciences, 2012)

Import and export of biological samples from tropical countries–considerations and guidelines for research teams - Swen C. Renner; Dirk Neumann; Michael Burkart; Ute Feit; Peter Giere; Andreas Gröger; Axel Paulsch; Cornelia Paulsch; Mario Sterz; Katrin Vohland (Organisms Diversity & Evolution, 2012)

Comparative analysis of phase I and II enzyme activities in 5 hepatic cell lines identifies Huh-7 and HCC-T cells with the highest potential to study drug metabolism - Jie Lin; Lilianna Schyschka; Ruben Mühl-Benninghaus; Jan Neumann; Liping Hao; Natascha Nussler; Steven Dooley; Liegang Liu; Ulrich Stöckle; Andreas K. Nussler; Sabrina Ehnert (Archives of Toxicology, 2012)

Could EST-based markers be used for the marker-assisted selection of drought tolerant barley (Hordeum vulgare) lines? - Fruzsina Szira; Andreas Börner; Kerstin Neumann; Khalil Zaynali Nezhad; Gábor Galiba; András Ferenc Bálint (Euphytica, 2011)

Inotropic effects of l-lysine in the mammalian heart - Andreas Boldt; Ulrich Gergs; Julia Frenker; Andreas Simm; Rolf-Edgar Silber; Udo Klöckner; Joachim Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

A positive inotropic effect of adenosine in cardiac preparations of right atria from diseased human hearts - Ulrich Gergs; Peter Boknik; Wilhelm Schmitz; Andreas Simm; Rolf-Edgar Silber; Joachim Neumann (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Phosphorylation of phospholamban and troponin I through 5-HT4 receptors in the isolated human atrium - Ulrich Gergs; Joachim Neumann; Andreas Simm; Rolf-Edgar Silber; Freerk Ole Remmers; Stephanie Läer (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Mutations in autism susceptibility candidate 2 (AUTS2) in patients with mental retardation - Vera M. Kalscheuer; David FitzPatrick; Niels Tommerup; Merete Bugge; Erik Niebuhr; Luitgard M. Neumann; Andreas Tzschach; Sarah A. Shoichet; Corinna Menzel; Fikret Erdogan; Ger Arkesteijn; Hans-Hilger Ropers; et al. (Human Genetics, 2007)

Holocene vegetation and climate history of the northern Golan heights (Near East) - Frank Neumann; Christian Schölzel; Thomas Litt; Andreas Hense; Mordechai Stein (Vegetation History and Archaeobotany, 2007)

Holocene vegetation and climate history of the northern Golan heights (Near East) - Frank Neumann; Christian Schölzel; Thomas Litt; Andreas Hense; Mordechai Stein (Vegetation History and Archaeobotany, 2007)

Seasonal nestmate recognition in the ant Formica exsecta - Andreas Katzerke; Peter Neumann; Christian W. W. Pirk; Peter Bliss; Robin F. A. Moritz (Behavioral Ecology and Sociobiology, 2006)

PIGY, a new plant envelope-class LTR retrotransposon - Pavel Neumann; Dana Požárková; Andrea Koblížková; Jiří Macas (Molecular Genetics and Genomics, 2005)

A multimodal brain-based feedback and communication system - Thilo Hinterberger; Nicola Neumann; Mirko Pham; Andrea Kbler; Anke Grether; Nadine Hofmayer; Barbara Wilhelm; Herta Flor; Niels Birbaumer (Experimental Brain Research, 2004)

Dritter ICA Mountain Cartography Workshop vom 15. bis 19. Mai 2002 am Mount Hood, Oregon, USA - Tobias Dahinden; Christian Häberling; Bernhard Jenny; Andreas Neumann; Stefän Räber; Lorenz Hurni (KN - Journal of Cartography and Geographic Information, 2004)

Further indications for genetic heterogeneity of euthyroid familial goiter - Susanne Neumann; Yvonne Bayer; Andreas Reske; Mria Tajtkov; Pavel Langer; Ralf Paschke (Journal of Molecular Medicine, 2003)

Glaziale und periglaziale Prozesse: Von der statischen zur dynamischen Visualisierung - Andreas Kääb; Yvonne Isakowski; Frank Paul; Andreas Neumann; Ramona Winter (KN - Journal of Cartography and Geographic Information, 2003)

First step towards a quantitative model describing Czc-mediated heavy metal resistance in Ralstonia metallidurans - Antje Legatzki; Sylvia Franke; Susann Lucke; Toni Hoffmann; Andreas Anton; Dieter Neumann; Dietrich H. Nies (Biodegradation, 2003)

Digitale Felsdarstellung für topographische Gebirgskarten - Lorenz Hurni; Andreas Neumann (KN - Journal of Cartography and Geographic Information, 1999)

Electrostatic determinants of the ion channel control of the nicotinic acetylcholine receptor of Torpedo californica - Andreas Kukol; E. Neumann (European Biophysics Journal, 1998)

Toxicity testing of heavy metals with theRhizobium-legume symbiosis: High sensitivity to cadmium and arsenic compounds - Heike Neumann; Anne Bode-Kirchhoff; Andrea Madeheim; Astrid Wetzel (Environmental Science and Pollution Research, 1998)

Productive expression state confers resistance of human immunodeficiency virus (HIV)-2-infected lymphoma cells against superinfection by HIV-1 - G. K. von Dalnok; Andrea Kleinschmidt; M. Neumann; Christine Leib-Moesch; V. Erfle; Ruth Brack-Werner (Archives of Virology, 1993)

Detection of developmentally regulated genes of the myxobacterium Stigmatella aurantiaca with the transposon Tn5lacZ - Andreas Pospiech; Bjrn Neumann; Barbara Silakowki; Hans Ulrich Schairer (Archives of Microbiology, 1993)